Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.3126/jbmr.v1i1.14550
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Remittance and Credit Disbursement of the Banking Sector: A Study from Bangladesh

Abstract: The paper investigates the relationships of remittance with credit disbursement of the banking sector in Bangladesh. The major portion of the remittance in Bangladesh is transferred through different banks as official channel. Besides, remittance recipient families transfer a portion of the remittance in the deposit accounts of different commercial banks. This two-way process helps to increase the liquidity position of the bank that enables them to increase the credit disbursement position of the banks. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 32 publications
0
1
0
Order By: Relevance
“…First, remittances might increase the demand for savings instruments considering that the fixed costs of sending remittances may cause the flows to be lumpy, thus providing households with excess cash for a certain period of time. As a result, this might potentially increase their demand for deposit accounts based on the fact that financial institutions offer households a safe place to store their temporary excess cash (Misati et al, 2019;Muktadir-Al-Mukit & Islam, 2016). Second, remittances might increase the chances of recipients in obtaining a loan from formal financial institutions or banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, remittances might increase the demand for savings instruments considering that the fixed costs of sending remittances may cause the flows to be lumpy, thus providing households with excess cash for a certain period of time. As a result, this might potentially increase their demand for deposit accounts based on the fact that financial institutions offer households a safe place to store their temporary excess cash (Misati et al, 2019;Muktadir-Al-Mukit & Islam, 2016). Second, remittances might increase the chances of recipients in obtaining a loan from formal financial institutions or banks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, contrary to Uprety's (2017) assertion that remittances are a curse for economic progress of Nepal, remittances do add to GDP and foreign exchange earnings of developing nations to a greater extent. Muktadir-Al-Mukit et al (2013) revealed that remittances were very important to both the migrant families and the country of balance of payments. As household income of migrant families rises due to the results of receiving remittances, they may have a tendency to spend more, which will raise the demand for imported items for consumption.…”
Section: Objectives and Hypothesis Of The Studymentioning
confidence: 99%
“…Remittances could result in higher prices for savings instruments, provided that the fixed expenses of receiving remittances increasing result in a lump-sum influx, presenting families with surplus cash over a certain length of time. Mostly as consequence, they can enhance their preference for deposit accounts on the basis that investment banks give families a safe capacity to sell their transient surplus capital (Misati et al, 2019;Muktadir-Al-Mukit & Islam, 2016).…”
Section: Introductionmentioning
confidence: 99%